Inter-individual variation in genes governing human hippocampal progenitor differentiation in vitro is associated with hippocampal volume in adulthood. Issue 1 (December 2017) - Powell, Timothy; Murphy, Tytus; Lee, Sang; Duarte, Rodrigo; Lee, Hyun Ah; Smeeth, Demelza; Price, Jack; Breen, Gerome; Thuret, Sandrine
Abstract Hippocampal volumes are smaller in psychiatric disorder patients and lower levels of hippocampal neurogenesis are the hypothesized cause. Understanding which molecular processes regulate hippocampal progenitor differentiation might aid in the identification of novel drug targets that can promote larger hippocampal volumes. Here we use a unique human cell line to assay genome-wide expression changes when hippocampal progenitor cells differentiate. RNA was extracted from proliferating cells versus differentiated neural cells and applied to Illumina Human HT-12 v4 Expression BeadChips. Linear regressions were used to determine the effect of differentiation on probe expression and we assessed enrichment for gene ontology (GO) terms. Genetic pathway analysis (MAGMA) was used to evaluate the relationship between hippocampal progenitor cell differentiation and adult hippocampal volume, using results from the imaging genomics consortium, ENIGMA. Downregulated transcripts were enriched for mitotic processes and upregulated transcripts were enriched for cell differentiation. Upregulated (differentiation) transcripts specifically, were also predictive of adult hippocampal volume; with Early growth response protein 2 identified as a hub transcription factor within the top GO term, and a potential drug target. Our results suggest that genes governing differentiation, rather than mitosis, have an impact on adult hippocampal volume and that these genes represent important drug targets.